The smart city – powerful but frightfully vulnerable? - Hult, Henrik; Granath, Hannes (2018)
Urban development has long been shaped and affected by technological development. The latest urban ideal is to invite the digital world to form the so called smart city. The smart city is arguably gaining momentum and its principles are becoming materialized in more and more cities around the world. As envisioned, this might just cast a shadow over previous technologies in terms of its ubiquitousness and its alleged potential for solving some of our times most urgent problems. However, our general concern is that the momentum and imagined solution-orientation towards urgent urban problems may override a constructive debate on whether the smart city is being rolled out in such a way as to enhance and not undermine the ability of cities to withstand and cope with stress while maintaining the ability to reorganize while undergoing change. In other words, is the smart city a friend or foe to the quest of building resilience? As a nascent urban development ideal, we think that this is an optimal time to begin mapping out challenges that the smart city poses and try to understand the societal implications thereof.